(untitled) (Al-Qamar, 2019)
This article presents the services of Shah Waliullah’s Family in Qur’ānic studies. It explains that Shah Waliullah started the work of understanding the Quran in a systematic manner in the subcontinent. Shah Waliullah was the first to translate the Qur’an. At a time when Muslims were declining in the subcontinent, Shah Waliullah started a movement to return to the Quran. He was the first to translate the Quran into Persian, because Persian was the most popular language at that time. The reason for choosing the title of Quranic services from the services of Shah Sahib is that if the work of renewing religion and reforming the Ummah is started in any age and in any country then the Quran will be given priority, without it the dream of revival of religion and nation cannot be fulfilled.